Semaphorins as Potential Immune Therapeutic Targets for Cancer - Jiang, Jun; Zhang, Fang; Wan, Yi; Fang, Ke; Yan, Ze-dong; Ren, Xin-ling; Zhang, Rui (Frontiers in Oncology, 2022)
Semaphorins are a large class of secreted or membrane-bound molecules. It has been reported that semaphorins play important roles in regulating several hallmarks of cancer, including angiogenesis, metastasis and immune evasion. Semaphorins and their receptors are widely expressed on tumor cells and immune cells. However, the biological role of semaphorins in tumor immune microenvironment is intricate. The dysregulation of semaphorins influences the recruitment and infiltration of immune cells, leading to abnormal anti-tumor effect. Although the underlying mechanisms of semaphorins on regulating tumor-infiltrating immune cell activation and functions are not fully understood, semaphorins can notably be promising immunotherapy targets for cancer.